Nurturing After Birth Obstetric Nurses as the First Line of Defense Against Sepsis - Kalvikkarasi Narayanaswamy; Sumathi Chandran; Shankar Shanmugam Rajendran; anitha Narayanasamy Naidu; Tamil Thendral Ravikumar; Sharmila Samson Jayaprakash; Meenakshi Prabhakar (The Bioscan, 2025)
Puerperal sepsis remains a major cause of maternal morbidity and mortality in low- and middle-income countries like India. Gaps in self-care and awareness among postnatal mothers increase this risk. Obstetric nurses play a key role in guiding mothers through structured education during the vulnerable postnatal period. The main objective of the study was to determine the effectiveness of an obstetric nurse-guided intervention on self-care practices for the prevention of puerperal sepsis and the level of well-being among postnatal mothers. METHODS AND MATERIALS: A quasi-experimental design was adopted among 60 postnatal mothers selected by purposive sampling and assigned to experimental (n=30) and control (n=30) groups. The experimental group received a four-week nurse-guided intervention on self-care, while the control group received routine care. Data were collected using validated tools (WHO-5 Well-Being Index, Modified Self-Care Questionnaire) and analysed with descriptive and inferential statistics. RESULT & DISCUSSION: Pre-test showed average self-care (86.7% experimental, 90% control) and poor well-being (60%, 53.3%). Post-test, good self-care (66.7% vs. 23.3%) and well-being (73.3% vs. 20%) improved in the experimental group (p<0.001). These results indicate that both demographic and clinical factors strongly influence postnatal self-care and well-being. Similar findings by Masih and Balusamy (2023) and McCauley et al. (2021) highlight the role of socioeconomic and contextual determinants in shaping maternal outcomes, reinforcing the need for tailored, context-specific postpartum interventions. CONCLUSION: Nurse-guided intervention improved postnatal self-care and well-being, reducing infection risk and supporting better maternal outcomes through structured care.